2012
DOI: 10.1002/jcc.23044
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of coinage metal fluoride and chloride clusters (MnFn and MnCln, M = Cu, Ag, or Au; n = 1–6)

Abstract: Calculations in the framework of the density functional theory are performed to study the lowest-energy isomers of coinage metal fluoride and chloride clusters (M(n) F(n) , M(n) Cl(n) , M = Cu, Ag, or Au, n = 1-6). For all calculated species starting from the trimers the most stable structures are found to be cyclic arrangements. However, planar rings are favored in the case of metal fluorides whereas metal chlorides prefer nonplanar cycles. Calculated bond lengths and infrared frequencies are compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 53 publications
4
28
0
Order By: Relevance
“…Metal clusters have attracted much experimental and theoretical research interest in the past few decades. Certain clusters consisting of a metal atom surrounded by electronegative atoms can display “superatom” behavior . These clusters, also known as “superhalogens,” can possess electron affinities (EA) that are even larger than that of a Cl atom, which has the highest EA in the periodic table.…”
Section: Introductionmentioning
confidence: 99%
“…Metal clusters have attracted much experimental and theoretical research interest in the past few decades. Certain clusters consisting of a metal atom surrounded by electronegative atoms can display “superatom” behavior . These clusters, also known as “superhalogens,” can possess electron affinities (EA) that are even larger than that of a Cl atom, which has the highest EA in the periodic table.…”
Section: Introductionmentioning
confidence: 99%
“…Rabilloud [9,10] reported values of 1.755/(2.00), 2.090/(2.33), 2.220/(2.44) and 2.390/(2.67) Å at B3LYP theoretical level with an spd function basis set (in their research, f-type functions were found not to give significant changes and so were not used). For binding energies, E b , the available experimental values of CuF, AgF and AgBr were 4.46, 3.64 and 2.88 eV; our CCSD(T) results are 4.43, 3.52 and 3.01 eV, while Rabilloud reported B3LYP values of 3.75, 3.05 and 2.60 eV.…”
Section: Structures and Stabilitiesmentioning
confidence: 94%
“…The question then arises if CM-halides are also covalent in character. The existence of d electrons in CMs makes theoretical investigations much more complicated, and the nature of CM-halide interactions remains controversial [9,10]. By analyzing electron localization function (ELF) results [11], Liu and coworkers [12] reported a strong ionic character in Au-F bonding and an increased covalent character from Au-Cl to Au-I in the [XAuCN] − (X=F−I) series.…”
Section: Introductionmentioning
confidence: 99%
“…An excellent review by Bellert and Breckenridge suggested that the XeAu + is described by a covalent bonding through an electrostatic model, while the nature of other NGAu + interactions is left undecided. Meanwhile, CM‐halides have also attracted many interests in terms of both experimental and theoretical investigations . Generally, the metal‐halides show ionic bonding characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…And obvious covalent bonding characteristics have been observed in Au‐containing compounds . Then the question arises whether the Au‐halides may in fact contain covalent characters and its nature is still controversial . Electron localization function (ELF) analyses on [XAuCN] − (X=F‐I) and MI 2 − (M=Cs, Cu, Au) found a strong ionic character in Au−F bonding and increased covalence from Au−Cl to Au‐I .…”
Section: Introductionmentioning
confidence: 99%